cis–trans Isomerization of silybins A and B - Novotná, Michaela; Gažák, Radek; Biedermann, David; Di Meo, Florent; Marhol, Petr; Kuzma, Marek; Bednárová, Lucie; Fuksová, Kateřina; Trouillas, Patrick; Křen, Vladimír (Beilstein Journal of Organic Chemistry, 2014)
Methods were developed and optimized for the preparation of the 2,3-cis- and the 10,11-cis-isomers of silybin by the Lewis acid catalyzed (BF3∙OEt2) isomerization of silybins A (1a) and B (1b) (trans-isomers). The absolute configuration of all optically pure compounds was determined by using NMR and comparing their electronic circular dichroism data with model compounds of known absolute configurations. Mechanisms for cis–trans-isomerization of silybin are proposed and supported by quantum mechanical calculations.
Keywords: 2,3-cis-silybin; 10,11-cis-silybin; isomerization; silibinin; silybin; silymarin